Porous diaphragm for flow battery and preparation method of porous diaphragm

By using the non-solvent-induced phase separation method in the liquid flow battery, porous base films are prepared and formed into polyelectrolyte nanoparticle rivet structures, the vanadium crossing, high cost and short life of the existing films are solved, and efficient and stable liquids are achieved Flow battery performance.

CN119297357APending Publication Date: 2025-01-10DONGHUA UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411712011.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The ion exchange membrane in existing flow batteries has problems such as vanadium crossing, high cost, short life and poor stability, making it difficult to maintain high efficiency in long-term use.

Method used

Porous base films are prepared by non-solvent-induced phase separation method, and a rivet structure of polyelectrolyte nanoparticles is formed on its surface, electrostatic adsorption to improve ion selectivity and conductivity while maintaining the stability of the film.

Benefits of technology

High proton conductivity, low vanadium ion permeability, low swelling rate and high dimensional stability are achieved, extending the service life of the membrane and improving the circulation stability of the flow battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297357A_ABST
    Figure CN119297357A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow batteries, and discloses a porous diaphragm for a flow battery and a preparation method thereof.The porous diaphragm comprises a polymer porous base membrane and polyelectrolyte nanoparticles which are electrostatically adsorbed on the surface of the polymer porous base membrane and openings of surface through holes, the polyelectrolyte nanoparticles are formed by cross-linking a polyanion electrolyte and a polycation electrolyte; the polyelectrolyte nano-particles are electrostatically adsorbed to openings of through holes in the surface of the polymer porous base membrane to form a rivet structure; the preparation method comprises the following steps: preparing a polymer porous base membrane from a polymer membrane casting solution in a non-solvent induced phase separation manner, then alternately soaking the polymer porous base membrane in an acidic salt solution of polycation electrolyte and a salt solution of polyanion electrolyte in sequence, and finally cross-linking in a cross-linking agent aqueous solution to obtain the porous diaphragm for the flow battery. The porous diaphragm prepared by the invention has high chemical stability, high dimensional stability and low vanadium ion permeability, and also has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries and relates to a porous diaphragm for a liquid flow battery and a preparation method thereof. Background Art

[0002] With the proposal of the goal of "carbon peak and carbon neutrality", the adjustment of the domestic energy structure has accelerated, and the gradual replacement of traditional fossil energy by new energy will also be a historical necessity. Renewable resources such as wind energy, tidal energy, and solar energy are intermittent and volatile, and direct integration into the power grid will encounter great difficulties and must be smoothed first. Redox flow battery (RFB), as a large-scale energy storage technology, can expand the energy storage capacity by adjusting the concentration or volume of the electrolyte without changing the total amount of active substances. It also has technical advantages such as high safety, long cycle life, and low self-discharge, so it has also been widely used.

[0003] All-vanadium liquid flow battery (VRFB) is the most important and promising technology in RFB. It is the only one that can be used in the field of wind power generation amplitude modulation, frequency modulation and smooth output grid connection so far, and has entered the stage of large-scale commercial demonstration operation and market development. Ion selective membrane is an important component of VRFB, and the physical and chemical properties of the membrane have a great influence on the battery efficiency. The ideal membrane should have high proton conductivity, low area specific resistance, low swelling rate, low vanadium ion crossover and good chemical and thermal stability. However, the VRFB that has been widely commercialized currently uses perfluorosulfonic acid (Nafion) membrane as the ion exchange membrane. However, VRFB involves a large number of cationic active substances, and Nafion membrane has serious vanadium crossover problems. At the same time, Nafion membrane has high cost and short life, which hinders its large-scale commercial application.

[0004] Compared with Nafion membrane, sulfonated polyetheretherketone (SPEEK) membrane has excellent ion selectivity, but in order to obtain higher ion conductivity, the sulfonation degree of SPEEK needs to be increased, which will cause the sulfonated polyetheretherketone membrane to swell and reduce stability. In the past decade, porous membranes have been used as ion-selective membranes in VRFBs because of their low cost, high stability and high ion conductivity. Porous membranes transport ions through pores or channels, and their ion selectivity depends on the size of the surface pores, and the ion conductivity depends on the through pores in the vertical direction. The porous membrane prepared by the non-solvent induced phase separation (NIPS) method has a dense surface and through pores in the vertical direction. Ideally, a dense and thick surface layer should be formed to achieve high ion selectivity, but this will reduce the size and density of the vertical pores, which is not conducive to improving ion conductivity. Therefore, traditional ion exchange membranes and porous membranes need to make a trade-off between ion selectivity and conductivity.

[0005] At present, the methods for controlling the pore size of porous membranes are mostly to coat the surface with a layer of inorganic materials with smaller pore size (for example: titanium dioxide, mesoporous silica, etc.), covalent organic frameworks (COF) or organic metal frameworks (MOF), etc. However, since liquid flow batteries are large-scale energy storage devices for long-term use, long-term stable use is also very important. However, there is no interaction between the modified coating coated on the surface and the base membrane. Long-term use will cause powder loss and peeling, and the performance will decrease accordingly. Therefore, having a stable structure that can be used stably for a long time in liquid flow batteries is also an important indicator.

[0006] For example, patent CN114628717B discloses a metal organic framework compound composite membrane and its preparation and application. The patent is a MOF composite membrane prepared by spraying a layer of metal organic framework compound (MOF) on a porous base membrane. However, the thickness of the MOF layer in the prepared MOF composite membrane is 1 to 5 μm, and the increase in the thickness of the surface layer will make the proton transmission channel tortuous, reducing the proton conductivity, and the spraying process makes the COF layer and the base membrane interface easy to peel off, which cannot meet the long-term operation of the flow battery.

[0007] For example, patent CN115198329A discloses inorganic alumina membrane and composite membrane for flow battery, preparation method thereof and flow battery. This patent uses an inorganic alumina composite membrane for VRFB. The average pore size of the prepared composite membrane is 0.5-20nm, which can effectively inhibit the penetration of vanadium ions. Alumina is hydrophilic and can improve proton conductivity. However, alumina is coated on the membrane surface by coating and other methods, and long-term use will produce "powder loss" phenomenon, reducing the performance of the composite membrane. At the same time, alumina is obtained by acid treatment of aluminum plate, while VRFB is a strong acid environment. During use, the strong acid will gradually corrode, resulting in low chemical stability, which cannot meet the actual application requirements of VRFB.

[0008] For example, the document "High Ion Conductive and Selective Membrane Achieved through Dual Ion Conducting Mechanisms[J]. Small, January 2023." discloses a dual-functional ion selective porous membrane, which is prepared by coating a polyetherimide porous base membrane with a Nafion emulsion-doped porous boron nitride (PBN), wherein the Nafion-PBN layer is between 2-7 μm. Although the thicker surface layer can reduce the permeability of vanadium ions, PBN is a porous nanomaterial and its distribution in the Nafion emulsion is not continuous, which makes the proton channel long and tortuous, reducing the ionic conductivity. At the same time, the Nafion-PBN layer is only attached to the porous base membrane by physical coating, which is difficult to maintain stability in the VRFB for a long time and cannot meet the long-term use requirements of the VRFB.

[0009] In summary, it is of great significance to study a porous membrane for liquid flow batteries and a preparation method thereof that has high proton conductivity, low vanadium ion permeability, high chemical stability, high dimensional stability and high interface bonding strength, and has a long-term stable life, in order to solve the above problems. Summary of the invention

[0010] The purpose of the present invention is to solve the problems existing in the prior art and provide a porous membrane for a flow battery and a preparation method thereof. The present invention first synthesizes a base membrane with through pores by a non-solvent induced phase separation method, such as Figure 1 As shown, polyelectrolyte nanoparticles are generated on the surface of the base membrane and the mouth of the through-holes on the surface through the layer assembly and chemical cross-linking, and are electrostatically adsorbed on the mouth of the through-holes on the surface of the polymer porous base membrane to form a rivet structure, which will not affect the internal through-holes, improve the ion selectivity but will not affect the ion conductivity. The polyelectrolyte nanoparticles act on the base membrane in a "rivet" structure, and the structure is stable, and will not peel off during the long-term use of the flow battery.

[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0012] A porous diaphragm for a flow battery, comprising a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking a polyanion electrolyte and a polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure;

[0013] The pore size of the polymer porous base membrane is 50nm~10μm, and the porosity is 70%~90%; the average particle size of the polyelectrolyte nanoparticles is 1~50nm, and the pores between the polyelectrolyte nanoparticles are 0.1~5nm. There are pores between the polyelectrolyte nanoparticles, and the pores are the pore size of the porous diaphragm for liquid flow batteries.

[0014] To ensure the formation of the rivet structure, the present application has special requirements on the pore size of the base membrane and the pore size of the polyelectrolyte nanoparticles formed by cross-linking of polyanionic electrolytes and polycationic electrolytes - the pore size of the polymer porous base membrane is 50nm~10μm, the average particle size of the polyelectrolyte nanoparticles is 1~50nm, and the particle size of the polyelectrolyte nanoparticles is not larger than the pore size of the polymer porous base membrane, thereby ensuring the possibility of entering the base membrane pores.

[0015] As the preferred technical solution:

[0016] In the porous membrane for a flow battery as described above, polyelectrolyte nanoparticles are electrostatically adsorbed on the mouths of through holes on the surface of the polymer porous base membrane to form a rivet structure, and the rivet depth is 10 to 200 nm.

[0017] The porous membrane for a liquid flow battery as described above has an ion conductivity of 60 to 120 mS·cm -1 The vanadium ion permeability is 2×10 -7 ~25×10 -7 cm 2 ·min -1 The swelling rate is 0.2-1%, which means there is almost no swelling. This indicates that the membrane will not decompose due to swelling that destroys the molecular structure during long-term circulation, and the dimensional stability is high.

[0018] The present invention also provides a method for preparing a porous diaphragm for a flow battery as described in any one of the above items, comprising the following steps:

[0019] (1) preparing a polymer casting solution with a mass concentration of 15 to 25%, and preparing a polymer porous base membrane by non-solvent induced phase separation;

[0020] (2) soaking the polymer porous base membrane obtained in step (1) alternately in an acidic salt solution of a polycation electrolyte and a salt solution of a polyanion electrolyte, and obtaining a precursor of the polymer porous membrane by layer-by-layer adsorption;

[0021] (3) The precursor of the polymer porous membrane obtained in step (2) is cross-linked in an aqueous solution of a cross-linking agent, and after the treatment is completed, a porous diaphragm for a liquid flow battery is obtained.

[0022] As the preferred technical solution:

[0023] In the method for preparing a porous membrane for a flow battery as described above, the polymer in step (1) is polyetherimide, polyimide, polysulfone or polyacrylonitrile;

[0024] A pore-forming agent is also added to the polymer casting solution. The pore-forming agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, glycerol and dibutyl phthalate. The amount of the pore-forming agent is 1-10% of the mass of the polymer.

[0025] According to the method for preparing a porous diaphragm for a liquid flow battery as described above, in step (1), a polymer porous base membrane is prepared by non-solvent induced phase separation. The specific process is: pouring a polymer casting liquid with a pore-forming agent added onto a glass plate, spreading it evenly using a scraper, and then placing it in a coagulation bath for phase separation for 24 hours to obtain a polymer porous base membrane; the coagulation bath is one or more of deionized water and alcohol solvents.

[0026] In the method for preparing a porous diaphragm for a flow battery as described above, step (2) is specifically as follows:

[0027] (2.1) adding a polyanion electrolyte and sodium chloride into water to prepare a polyanion electrolyte salt solution;

[0028] (2.2) Adding a polycation electrolyte and sodium chloride into water to prepare a polycation electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 5-6, because the prepared polycation electrolyte salt solution must be protonated to have an electrostatic adsorption effect, and the protonation result can only be achieved by adjusting the pH to an acidic level. After the adjustment is completed, an acidic polycation electrolyte salt solution is obtained;

[0029] (2.3) The polymer porous base membrane is immersed in an acidic salt solution of a polycation electrolyte for 15 minutes, taken out and rinsed with deionized water, and then immersed in a salt solution of a polyanion electrolyte for 15 minutes, taken out and rinsed with deionized water, and this operation is repeated 6 to 10 times to obtain a precursor of the polymer porous membrane; during the immersion process, since the polymer porous base membrane is negatively charged, the polycation electrolyte is positively charged, and the polyanion electrolyte is negatively charged, based on the principle that opposite charges attract and like charges repel, it is necessary to first adsorb the polycation electrolyte and then the polyanion electrolyte, so that the polycation electrolyte can enter the pores first with the help of attraction, and then the polyanion electrolyte enters the pores, and the polyanion electrolyte and the polycation electrolyte are cross-linked inside the pores, and finally a rivet structure of a certain depth is formed in the pores after multiple alternating depositions.

[0030] In the method for preparing a porous diaphragm for a flow battery as described above, in step (2.1), the mass ratio of sodium chloride to polyanion electrolyte is 2.5 to 20:1, and the amount ratio of polyanion electrolyte to water is 1 g:50 to 200 ml;

[0031] In step (2.2), the mass ratio of sodium chloride to polycationic electrolyte is 2.5-20:1, and the amount ratio of polycationic electrolyte to water is 1g:50-200ml;

[0032] The role of sodium chloride is to adjust the degree of aggregation of polyelectrolytes. By adjusting different salt concentrations, the size of the optimal agglomerated particles of the polyelectrolyte layer can be achieved to match the size of the pores on the surface of the base membrane, thereby achieving excellent ion selectivity.

[0033] In the method for preparing a porous diaphragm for a liquid flow battery as described above, the polyanion electrolyte in step (2.1) is lignin sulfonate, polyacrylic acid salt or polystyrene sulfonate, but is not limited to these. Lignin sulfonate, polyacrylic acid salt and polystyrene sulfonate are polyanion electrolytes containing a large number of charged groups, which improve the water solubility of the base membrane and the sulfonic acid groups or carboxylic acid groups contained can also provide additional active sites for constructing a hydrogen binding network, thereby promoting the rapid transport of protons inside the liquid flow battery; in step (2.2), the polycationic electrolyte is polyethyleneimine, polyacrylamine hydrochloride or polyvinylpyridine, but is not limited to these.

[0034] In the method for preparing a porous diaphragm for a liquid flow battery as described above, the mass concentration of the crosslinking agent aqueous solution in step (3) is 1-2%, the crosslinking agent is an aldehyde or an acid anhydride, the aldehyde is glyoxal, formaldehyde or glutaraldehyde, the acid anhydride is trimesoyl chloride, dimethyl phthalate or maleic anhydride, but is not limited to the above-mentioned types of crosslinking agents; the temperature of the crosslinking treatment is 60-80°C, and the time is 1-2h.

[0035] Beneficial effects:

[0036] (1) The present invention can achieve the regulation of the pore size of the porous diaphragm for liquid flow batteries by controlling the number of times the polyelectrolyte nanoparticles are electrostatically adsorbed on the polymer porous base membrane, and effectively block the penetration of vanadium ions through the pore size screening effect. At the same time, the polyelectrolyte nanoparticles exist on the base membrane in a "rivet" structure, which will not affect the internal through holes, thereby improving the ion selectivity and having a stable structure. During the long-term use of the liquid flow battery, no peeling phenomenon will occur.

[0037] (2) The method for preparing a porous membrane for a liquid flow battery of the present invention is simple, convenient and inexpensive. The prepared porous membrane for a liquid flow battery has the advantages of adjustable pore size, high ion conductivity, excellent vanadium ion permeability and high dimensional stability. When used in a liquid flow battery, the cycle stability of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a cross-sectional schematic diagram of a porous diaphragm for a liquid flow battery of the present invention;

[0039] Figure 2 This is an electron microscope image of a cross section of a porous diaphragm for a flow battery prepared in Example 2 of the present invention;

[0040] Figure 3 Schematic diagram of the surface of the porous diaphragm for a flow battery prepared in Example 1 of the present invention before and after being adhered with 3M tape;

[0041] Figure 4 Schematic diagram of the comparison of vanadium permeation between the porous membrane for flow battery prepared in Example 1 and the Nafion membrane for 72 hours;

[0042] Figure 5 This is an electron microscope image of the surface of the porous diaphragm for a flow battery prepared in Example 3;

[0043] Figure 6 This is an electron microscope image of the cross section of the porous diaphragm for a liquid flow battery prepared in Example 3 of the present invention, wherein the circled area in the image is the rivet structure. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0045] The testing methods of the relevant performance indicators in the following embodiments are as follows:

[0046] Vanadium ion permeability: H-type electrolytic cell (effective area 2.0096cm 2 ) The vanadium ion permeability of the porous membrane for flow battery prepared in each embodiment was tested. First, 15 mL of solution A (composed of VOSO 4 , H 2 SO 4 Mixed with water, VOSO 4 The concentration of H 2 SO 4 The concentration is 3 M), and 15 mL of solution B (composed of MgSO 4 , H 2 SO 4 Mixed with water, MgSO 4 The concentration of H 2 SO 4 The concentration is 3M), and then 2mL of solution B is collected from the right chamber as a sample every 12h, and the unused 2mL of solution B is added to the right chamber to keep the volume on both sides the same. Finally, the absorbance of the sample at a wavelength of 760nm is measured by ultraviolet light, and then a standard curve is obtained based on the measured data. The standard curve is then used to calculate the permeability of vanadium ions from the concentration of each measured absorbance. The calculation formula is: Where V is the volume of the solution on the right (in mL), and A is the effective area of ​​the membrane (in cm 2 ), L is the thickness of the porous membrane for flow battery (in cm), C 0 Left VOSO 4 The initial concentration, C t Right middle VO2+ The concentration at time t, P is the permeability.

[0047] Swelling rate: First, the porous membrane for flow battery prepared in each embodiment is used as a sample. Three samples of the same kind are prepared and completely immersed in deionized water for 24 hours. Then, the three samples are taken out and the moisture on the flat surface of the samples is wiped dry with absorbent paper. The length (L) of each sample after immersion is measured and recorded. wet ), and then put the soaked samples into an oven at 80°C and dry them for 24 hours, and then measure their length (L dry ), and finally the swelling rate is calculated by using the calculation formula for the values ​​of each of the three samples. Finally, the swelling rate obtained from the three samples is averaged, and the calculation formula for the swelling rate is:

[0048] Ionic conductivity: The porous membranes for flow batteries prepared in each example were used as samples. The samples were clamped in a chamber filled with H at 25 °C. 2 SO 4 (concentration of 1M) in a conductive tank, and then use the electrochemical impedance spectroscopy of the electrochemical workstation to measure the resistance of the sample. Finally, the conductivity is obtained by the calculation formula based on the measured data. The calculation formula is: Where, L is the thickness of the porous membrane used in the flow battery; R s is the resistance of a porous diaphragm for flow batteries, R 0 is the resistance when there is no porous membrane for flow battery; A is the effective area of ​​the porous membrane for flow battery.

[0049] Example 1

[0050] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0051] (1) preparing a polyetherimide porous base membrane;

[0052] A polyetherimide casting solution with a mass concentration of 15% (composed of polyetherimide (manufacturer: Shanghai Titan Technology Co., Ltd., brand name: Adamas, item number: 013658786) and N-methylpyrrolidone) was prepared, and polyvinylpyrrolidone (manufacturer: Shanghai Titan Technology Co., Ltd., brand name: Adamas, item number: 011006796, molecular weight: K30) was added to the polyetherimide casting solution, the polyetherimide casting solution with polyvinylpyrrolidone added was poured onto a glass plate, and evenly spread using a film scraper, and then placed in deionized water for phase separation for 24 hours to obtain a polyetherimide porous base membrane; wherein the amount of the pore-forming agent was 1% of the mass of the polyetherimide;

[0053] The obtained polyetherimide porous base membrane has a pore size of 50nm to 10μm and a porosity of 90%;

[0054] (2) preparing a precursor of a polymer porous membrane;

[0055] (2.1) Adding a polyanion electrolyte (sodium lignin sulfonate, manufactured by Shanghai Yuanye Biotechnology Co., Ltd., product number S30635) and sodium chloride into water to prepare a polyanion electrolyte salt solution; wherein the mass ratio of sodium chloride to polyanion electrolyte is 5:1, and the amount ratio of polyanion electrolyte to water is 1 g:100 ml;

[0056] (2.2) adding polycationic electrolyte (polyethyleneimine, manufactured by Sane Chemical Technology (Shanghai) Co., Ltd., brand name Anaiji, product number D110147) and sodium chloride to water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 5 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 5:1, and the amount ratio of polycationic electrolyte to water is 1 g:100 ml;

[0057] (2.3) soaking the polyetherimide porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation 10 times to obtain a precursor of a polymer porous membrane;

[0058] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 1 hour, and then rinsing with deionized water and drying in sequence to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is glyoxal, the mass concentration of the cross-linking agent aqueous solution is 1%, and the cross-linking temperature is 60°C.

[0059] The finally prepared porous membrane for liquid flow battery comprises a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking of polyanion electrolyte and polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure, the rivet depth is 50nm, the average particle size of the polyelectrolyte nanoparticles is 10nm, and the average pores between the polyelectrolyte nanoparticles are 0.1nm; the thickness of the porous membrane for liquid flow battery is 125μm, and the ion conductivity is 60mS·cm -1 The vanadium ion permeability is 2×10 -7 cm 2 ·min -1 , the swelling rate is 0.2%;

[0060] The porous membrane for flow battery prepared above was pasted with 3M tape to test the structural stability of the polyelectrolyte nanoparticle layer. The surface of the porous membrane for flow battery before and after pasting was as follows: Figure 3 As shown in the figure, it can be seen that before and after the porous diaphragm for liquid flow battery prepared by the present invention is pasted with 3M glue, no powdering, peeling and the like phenomenon occurs, indicating that the porous diaphragm for liquid flow battery prepared by the present invention has good stability and can be used in liquid flow battery for a long time;

[0061] At the same time, the vanadium ion permeability of the porous membrane for liquid flow battery prepared above was compared with that of Nafion membrane (manufacturer is DuPont Company, USA, brand name is Nafion115). Figure 4 As shown in the figure, it can be seen that the vanadium ion permeability of the porous membrane for liquid flow battery prepared by the present invention is much lower than that of the Nafion membrane, which effectively blocks the penetration of vanadium ions.

[0062] Example 2

[0063] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0064] (1) preparing a polyimide porous base membrane;

[0065] A polyimide casting solution with a mass concentration of 20% (composed of polyimide (manufacturer: Shanghai Titan Technology Co., Ltd., brand name: Adamas, item number: 013658177) and N,N-dimethylacetamide) was prepared, and polyethylene glycol (manufacturer: Shanghai Titan Technology Co., Ltd., brand name: Greagent, item number: 013674102) was added to the polyimide casting solution, the polyimide casting solution with polyethylene glycol added was poured onto a glass plate, and a film scraper was used to spread it evenly, and then it was placed in deionized water for phase separation for 24 hours to obtain a polyimide porous base membrane; wherein, the amount of the pore-forming agent was 5% of the mass of the polyimide;

[0066] The obtained polyimide porous base membrane has a pore size of 50 nm to 10 μm and a porosity of 90%;

[0067] (2) preparing a precursor of a polymer porous membrane;

[0068] (2.1) Adding polyanion electrolyte (sodium polyacrylate, manufactured by Shanghai Titan Technology Co., Ltd., brand Adamas, product number 013631362) and sodium chloride into water to prepare a salt solution of polyanion electrolyte; wherein the mass ratio of sodium chloride to polyanion electrolyte is 2.5:1, and the amount ratio of polyanion electrolyte to water is 1 g:100 ml;

[0069] (2.2) adding polycationic electrolyte (polyacrylamine hydrochloride, manufactured by Shanghai Titan Technology Co., Ltd., brand Adamas, product number 01484480) and sodium chloride to water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 6 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 2.5:1, and the amount ratio of polycationic electrolyte to water is 1 g:100 ml;

[0070] (2.3) soaking the polyimide porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation 8 times to obtain a precursor of a polymer porous membrane;

[0071] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 1.5 h, and then rinsing with deionized water and drying in sequence to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is formaldehyde, the mass concentration of the cross-linking agent aqueous solution is 1.5%, and the cross-linking temperature is 70°C.

[0072] The porous membrane for liquid flow battery finally prepared includes a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking a polyanion electrolyte and a polycation electrolyte; Figure 2 As shown in the figure, the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure. The rivet depth is 10nm, the average particle size of the polyelectrolyte nanoparticles is 1nm, and the average pores between the polyelectrolyte nanoparticles are 2.5nm. The thickness of the porous membrane for the flow battery is 115μm, and the ionic conductivity is 90mS·cm -1 The vanadium ion permeability is 12×10 -7 cm 2 ·min -1 , the swelling rate is 0.5%.

[0073] Example 3

[0074] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0075] (1) preparing a polysulfone porous base membrane;

[0076] A polysulfone casting solution with a mass concentration of 25% (composed of polysulfone (manufacturer: Shanghai Myrel Biochemical Technology Co., Ltd., product number: M60464) and N,N-dimethylacetamide) was prepared, and glycerol (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., product number: G116203) was added to the polysulfone casting solution, the polysulfone casting solution with glycerol added was poured onto a glass plate, and a film scraper was used to spread it evenly, and then it was placed in a mixture of deionized water and isopropanol with a volume ratio of 1:1 for phase separation for 24 hours to obtain a polysulfone porous base membrane; wherein, the amount of the pore-forming agent was 10% of the mass of the polysulfone;

[0077] The obtained polysulfone porous base membrane has a pore size of 100 nm to 1 μm and a porosity of 80%;

[0078] (2) preparing a precursor of a polymer porous membrane;

[0079] (2.1) Adding polyanion electrolyte (sodium polystyrene sulfonate, manufactured by Sinopharm Chemical Reagent Co., Ltd., specification: Acros-C22227) and sodium chloride into water to prepare a salt solution of polyanion electrolyte; wherein the mass ratio of sodium chloride to polyanion electrolyte is 20:1, and the amount ratio of polyanion electrolyte to water is 1 g:150 ml;

[0080] (2.2) adding polycationic electrolyte (polyvinyl pyridine, manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd., product number P303220) and sodium chloride into water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 5 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 20:1, and the amount ratio of polycationic electrolyte to water is 1 g:150 ml;

[0081] (2.3) soaking the polysulfone porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation 6 times to obtain a precursor of a polymer porous membrane;

[0082] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 2 h, and then rinsing with deionized water and drying in sequence to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is glutaraldehyde, the mass concentration of the cross-linking agent aqueous solution is 2%, and the cross-linking temperature is 80°C.

[0083] like Figure 5As shown, the porous membrane for liquid flow battery finally prepared includes a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, and the polyelectrolyte nanoparticles are formed by cross-linking a polyanion electrolyte and a polycation electrolyte; Figure 6 As shown in the figure, the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure. The rivet depth is 200nm, the average particle size of the polyelectrolyte nanoparticles is 50nm, and the average pores between the polyelectrolyte nanoparticles are 5nm. The thickness of the porous membrane for the flow battery is 110μm, and the ionic conductivity is 120mS·cm -1 The vanadium ion permeability is 25×10 -7 cm 2 ·min -1 , the swelling rate is 1%.

[0084] Example 4

[0085] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0086] (1) preparing a porous polyacrylonitrile base membrane;

[0087] A polyacrylonitrile casting solution with a mass concentration of 15% (composed of polyacrylonitrile (manufacturer: Shanghai Titan Technology Co., Ltd., brand: Adamas, item number: 013358770) and N-methylpyrrolidone) was prepared, and dibutyl phthalate was added to the polyacrylonitrile casting solution, the polyacrylonitrile casting solution with dibutyl phthalate added was poured onto a glass plate, and a film scraper was used to spread it evenly, and then it was placed in a mixture of deionized water and ethanol with a volume ratio of 1:1 for phase separation for 24 hours to obtain a polyacrylonitrile porous base membrane; wherein the amount of the pore-forming agent was 5% of the mass of the polyacrylonitrile;

[0088] The obtained polyacrylonitrile porous base membrane has a pore size of 100 nm to 2 μm and a porosity of 85%;

[0089] (2) preparing a precursor of a polymer porous membrane;

[0090] (2.1) Adding polyanion electrolyte (alkaline lignin, manufactured by Sane Chemical Technology (Shanghai) Co., Ltd., brand name Anaiji, CAS number 8068-05-1, product number D110168) and sodium chloride into water to prepare a salt solution of polyanion electrolyte; wherein the mass ratio of sodium chloride to polyanion electrolyte is 15:1, and the amount ratio of polyanion electrolyte to water is 1 g:200 ml;

[0091] (2.2) adding polycationic electrolyte (polyacrylamine hydrochloride, manufactured by Shanghai Titan Technology Co., Ltd., brand Adamas, product number 01484480) and sodium chloride to water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 5.5 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 15:1, and the amount ratio of polycationic electrolyte to water is 1 g:200 ml;

[0092] (2.3) soaking the polyacrylonitrile porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation 10 times to obtain a precursor of a polymer porous membrane;

[0093] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 1 hour, and then successively rinsing with deionized water and drying to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is trimesoyl chloride, the mass concentration of the cross-linking agent aqueous solution is 1%, and the cross-linking temperature is 60°C.

[0094] The finally prepared porous membrane for liquid flow battery comprises a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking of polyanion electrolyte and polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure, the rivet depth is 100nm, the average particle size of the polyelectrolyte nanoparticles is 25nm, and the average pores between the polyelectrolyte nanoparticles are 0.5nm; the thickness of the porous membrane for liquid flow battery is 120μm, and the ion conductivity is 75mS·cm -1 The vanadium ion permeability is 7×10 -7 cm 2 ·min -1 , the swelling rate is 0.6%.

[0095] Example 5

[0096] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0097] (1) preparing a polyetherimide porous base membrane;

[0098] A polyetherimide casting solution with a mass concentration of 20% (composed of polyetherimide (manufacturer: Shanghai Titan Technology Co., Ltd., brand name: Adamas, item number: 013658786) and N-methylpyrrolidone) was prepared, and a mixture of glycerol (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., item number: G116203) and dibutyl phthalate in a mass ratio of 1:1 was added to the polyetherimide casting solution, and the polyetherimide casting solution with the mixture of glycerol and dibutyl phthalate added was poured onto a glass plate, and a film scraper was used to spread it evenly, and then it was placed in ethanol for phase separation for 24 hours to obtain a polyetherimide porous base membrane; wherein the amount of the pore-forming agent was 10% of the mass of the polyetherimide;

[0099] The obtained polyetherimide porous base membrane has a pore size of 50 nm to 1 μm and a porosity of 70%;

[0100] (2) preparing a precursor of a polymer porous membrane;

[0101] (2.1) Adding polyanion electrolyte (sodium polystyrene sulfonate, manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: Acros-C22227) and sodium chloride into water to prepare a salt solution of polyanion electrolyte; wherein the mass ratio of sodium chloride to polyanion electrolyte is 5:1, and the amount ratio of polyanion electrolyte to water is 1 g:50 ml;

[0102] (2.2) adding polycationic electrolyte (polyethyleneimine, manufactured by Sane Chemical Technology (Shanghai) Co., Ltd., brand name Anaiji, product number D110147) and sodium chloride to water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 6 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 5:1, and the amount ratio of polycationic electrolyte to water is 1 g:50 ml;

[0103] (2.3) soaking the polyetherimide porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation 6 times to obtain a precursor of a polymer porous membrane;

[0104] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 2 hours, and then successively rinsing with deionized water and drying to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is dimethyl phthalate, the mass concentration of the cross-linking agent aqueous solution is 2%, and the cross-linking temperature is 80°C.

[0105] The finally prepared porous membrane for liquid flow battery includes a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking of polyanion electrolyte and polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure, the rivet depth is 50nm, the average particle size of the polyelectrolyte nanoparticles is 10nm, and the average pores between the polyelectrolyte nanoparticles are 4nm; the thickness of the porous membrane for liquid flow battery is 112μm, and the ion conductivity is 105mS·cm -1 The vanadium ion permeability is 17×10 -7 cm 2 ·min -1 , the swelling rate is 0.8%.

[0106] Example 6

[0107] A method for preparing a porous diaphragm for a flow battery, the steps are as follows:

[0108] (1) preparing a polyimide porous base membrane;

[0109] A polyimide casting solution with a mass concentration of 25% (composed of polyimide (manufacturer: Shanghai Titan Technology Co., Ltd., brand: Adamas, product number: 013658177) and N,N-dimethylacetamide) was prepared, the polyimide casting solution was poured onto a glass plate, and evenly spread using a scraper, and then placed in isopropanol for phase separation for 24 hours to obtain a polyimide porous base membrane;

[0110] The obtained polyimide porous base membrane has a pore size of 50 nm to 2 μm and a porosity of 75%;

[0111] (2) preparing a precursor of a polymer porous membrane;

[0112] (2.1) Adding polyanion electrolyte (polyacrylic acid, manufacturer: Shanghai Titan Technology Co., Ltd., brand name Adamas, product number 013629502) and sodium chloride into water to prepare a salt solution of polyanion electrolyte; wherein the mass ratio of sodium chloride to polyanion electrolyte is 10:1, and the amount ratio of polyanion electrolyte to water is 1 g:150 ml;

[0113] (2.2) adding polycationic electrolyte (polyvinyl pyridine, manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd., product number P303220) and sodium chloride into water to prepare a polycationic electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 6 to obtain an acidic polycationic electrolyte salt solution; wherein the mass ratio of sodium chloride to polycationic electrolyte is 10:1, and the amount ratio of polycationic electrolyte to water is 1 g:150 ml;

[0114] (2.3) soaking the polyimide porous base membrane obtained in step (1) in an acidic salt solution of a polycation electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and then soaking it in a salt solution of a polyanion electrolyte for 15 minutes, taking it out and rinsing it with deionized water, and repeating this operation for 9 times to obtain a precursor of a polymer porous membrane;

[0115] (3) Cross-linking the precursor of the polymer porous membrane obtained in step (2) in a cross-linking agent aqueous solution for 2 hours, and then successively rinsing with deionized water and drying to obtain a porous membrane for a liquid flow battery; wherein the cross-linking agent in the cross-linking agent aqueous solution is maleic anhydride, the mass concentration of the cross-linking agent aqueous solution is 1.5%, and the cross-linking temperature is 60°C.

[0116] The finally prepared porous membrane for liquid flow battery includes a polymer porous base membrane and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base membrane and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking of polyanion electrolyte and polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base membrane to form a rivet structure, the rivet depth is 25nm, the average particle size of the polyelectrolyte nanoparticles is 8nm, and the average pores between the polyelectrolyte nanoparticles are 1nm; the thickness of the porous membrane for liquid flow battery is 110μm, and the ion conductivity is 85mS·cm -1 The vanadium ion permeability is 9×10 -7 cm 2 ·min -1 , the swelling rate is 0.4%.

Claims

1. A porous membrane for a flow battery, characterized in that: The invention comprises a polymer porous base film and polyelectrolyte nanoparticles electrostatically adsorbed on the surface of the polymer porous base film and the mouth of the through holes on the surface, wherein the polyelectrolyte nanoparticles are formed by cross-linking a polyanion electrolyte and a polycation electrolyte; the polyelectrolyte nanoparticles are electrostatically adsorbed on the mouth of the through holes on the surface of the polymer porous base film to form a rivet structure; The pore size of the polymer porous base film is 50nm-10μm, and the porosity is 70%-90%; the average particle size of the polyelectrolyte nanoparticles is 1-50nm, and the pores between the polyelectrolyte nanoparticles are 0.1-5nm.

2. A porous membrane for a liquid flow battery according to claim 1, characterized in that: The polyelectrolyte nanoparticles are electrostatically adsorbed on the mouths of the through holes on the surface of the polymer porous base film to form a rivet structure, and the rivet depth is 10 to 200 nm.

3. A porous membrane for a liquid flow battery according to claim 2, characterized in that: The ionic conductivity of porous membranes for flow batteries is 60 to 120 mS·cm -1 The vanadium ion permeability is 2×10 -7 ~25×10 -7 cm 2 ·min -1 The swelling rate is 0.2~1%.

4. A method for preparing a porous membrane for a flow battery according to any one of claims 1 to 3, characterized in that: The steps include: (1) preparing a polymer casting solution with a mass concentration of 15 to 25%, and preparing a polymer porous base membrane by non-solvent induced phase separation; (2) soaking the polymer porous base membrane obtained in step (1) alternately in an acidic salt solution of a polycation electrolyte and a salt solution of a polyanion electrolyte, and obtaining a precursor of the polymer porous membrane by layer-by-layer adsorption; (3) The precursor of the polymer porous membrane obtained in step (2) is cross-linked in an aqueous solution of a cross-linking agent, and after the treatment is completed, a porous diaphragm for a liquid flow battery is obtained.

5. The method for preparing a porous diaphragm for a flow battery according to claim 4, characterized in that: In step (1), the polymer is polyetherimide, polyimide, polysulfone or polyacrylonitrile; A pore-forming agent is also added to the polymer casting solution. The pore-forming agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, glycerol and dibutyl phthalate. The amount of the pore-forming agent is 1-10% of the mass of the polymer.

6. The method for preparing a porous diaphragm for a flow battery according to claim 4, characterized in that: In step (1), a polymer porous base membrane is prepared by non-solvent induced phase separation. The specific process is: pouring a polymer casting solution to which a pore-forming agent is added onto a glass plate, spreading it evenly using a scraper, and then placing it in a coagulation bath for phase separation to obtain a polymer porous base membrane; the coagulation bath is one or more of deionized water and alcohol solvents.

7. The method for preparing a porous membrane for a flow battery according to claim 4, characterized in that: Step (2) is specifically as follows: (2.1) adding a polyanion electrolyte and sodium chloride into water to prepare a polyanion electrolyte salt solution; (2.2) adding a polycation electrolyte and sodium chloride into water to prepare a polycation electrolyte salt solution, and adding hydrochloric acid to adjust the pH to 5 to 6 to obtain an acidic polycation electrolyte salt solution; (2.3) The polymer porous base membrane is immersed in an acidic salt solution of a polycationic electrolyte for 15 minutes, taken out and rinsed with deionized water, and then immersed in a salt solution of a polyanion electrolyte for 15 minutes, taken out and rinsed with deionized water. This operation is repeated 6 to 10 times to obtain a precursor of the polymer porous membrane.

8. The method for preparing a porous diaphragm for a flow battery according to claim 7, characterized in that: In step (2.1), the mass ratio of sodium chloride to polyanion electrolyte is 2.5-20:1, and the amount ratio of polyanion electrolyte to water is 1g:50-200ml; In step (2.2), the mass ratio of sodium chloride to polycationic electrolyte is 2.5-20:1, and the dosage ratio of polycationic electrolyte to water is 1g:50-200ml.

9. The method for preparing a porous diaphragm for a flow battery according to claim 7, characterized in that: In step (2.1), the polyanion electrolyte is lignin sulfonate, polyacrylic acid salt or polystyrene sulfonate; in step (2.2), the polycation electrolyte is polyethyleneimine, polyacrylamine hydrochloride or polyvinylpyridine.

10. The method for preparing a porous diaphragm for a flow battery according to claim 4, characterized in that: The mass concentration of the crosslinking agent aqueous solution in step (3) is 1-2%, the crosslinking agent is an aldehyde or an acid anhydride, the aldehyde is glyoxal, formaldehyde or glutaraldehyde, and the acid anhydride is trimesoyl chloride, dimethyl phthalate or maleic anhydride; the temperature of the crosslinking treatment is 60-80° C., and the time is 1-2 hours.

Citation Information

Cited By

  • Heterogeneous polyelectrolyte self-assembled membrane as well as preparation method and application thereof

    CN120109248A